Serum Level and Genetic Polymorphism of IL-38 and IL-40 in Autoimmune Thyroid Disease - Abed, Reema Mohammed; Abdulmalek, Hadeel Waleed; Yaaqoob, Laith Ahmad; Altaee, Maha Fakhry; Kamona, Zaid K. (Iraqi Journal of Science, 2023)
Autoimmune thyroid disease mainly includes Graves’ disease (GD) and autoimmune hypothyroidism (AIH), which is caused by individual genetics, autoimmune dysfunction, and a variety of external environmental factors. Interleukin IL-38 and IL- 40 are involved in a wide range of autoimmune diseases, but little is known about IL-38 and IL-40 expression in autoimmune thyroid disease. This research included 82 female patients with Graves' disease (GD), 78 females with autoimmune hypothyroidism (AIH), and 85 female healthy controls (HC). An enzyme linked immunosorbent assay and sequencing of IL-38 and IL-40 were used to evaluate serum levels and gene polymorphism, respectively. Results showed that significantly lower level of serum IL-38 levels in the GD and AIH groups in comparison with HC group (both p 0.0001). While there were highly significant differences in the GD and AIH groups than in the HC population (both p 0.0001). There was a significant variability in genotype and allele frequencies in the promoter region of IL-38 and IL-40 genes between patients with thyroid disease and healthy controls. The IL-38 homozygote genotype GG exhibits a substantial correlation with GD (P=0.000). While the CC genotype of IL-40 was shown to have a significant correlation with AIH. The findings suggest that serum concentrations of IL-38 and IL-40 are potential novel diagnostic biomarkers in patients with GD and AIH, and that the homozygotes GG and CC of IL-38 and IL-40, respectively, serve as a potential predisposing factor on GD and AIH development in the Iraqi population.